(untitled) (Academicia Globe: Inderscience Research, 2024)
This article discusses the works of portrait artists about the state of the woman and the scientific theoretical foundations of the portrait . The works provide information about the palette of colors, the state of the images and their interpretation, the singing of our national values, and their philosophical ideas.